2018
DOI: 10.1098/rsob.180068
|View full text |Cite
|
Sign up to set email alerts
|

Controllable oxidative stress and tissue specificity in major tissues during the torpor–arousal cycle in hibernating Daurian ground squirrels

Abstract: Mammalian hibernators experience repeated hypoxic ischaemia and reperfusion during the torpor–arousal cycle. We investigated levels of oxidative stress, antioxidant capacity, and the underlying mechanism in heart, liver, brain and kidney tissue as well as plasma during different periods of hibernation in Daurian ground squirrels (Spermophilus dauricus). Our data showed that the levels of hydrogen peroxide significantly increased in the heart and brain during late torpor (LT) compared with levels during the sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 53 publications
4
39
1
Order By: Relevance
“…Several elements of the H2S-Nrf2-antioxidant proteins axis have been assessed in hibernating species in previous studies [10,23,[33][34][35][36][37]; however, to our knowledge, this is the first time that all the components of this axis were evaluated mechanistically. Additionally, and contrary to previous studies [10,23,[33][34][35][36][37], we assessed the activity and the outcome of the H2S-Nrf2-antioxidant proteins axis in a native hibernator, not under cold anoxia-reoxygenation conditions, but under warm anoxia-reoxygenation conditions, such are the conditions encountered in clinical practice. However, the available data about the protective role of H 2 S in hamster renal cells subjected to cold anoxia-reoxygenation may be proven useful in the field of solid organ transplantation, and more precisely, in graft preservation [10,38].…”
Section: Discussionmentioning
confidence: 99%
“…Several elements of the H2S-Nrf2-antioxidant proteins axis have been assessed in hibernating species in previous studies [10,23,[33][34][35][36][37]; however, to our knowledge, this is the first time that all the components of this axis were evaluated mechanistically. Additionally, and contrary to previous studies [10,23,[33][34][35][36][37], we assessed the activity and the outcome of the H2S-Nrf2-antioxidant proteins axis in a native hibernator, not under cold anoxia-reoxygenation conditions, but under warm anoxia-reoxygenation conditions, such are the conditions encountered in clinical practice. However, the available data about the protective role of H 2 S in hamster renal cells subjected to cold anoxia-reoxygenation may be proven useful in the field of solid organ transplantation, and more precisely, in graft preservation [10,38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Orr et al (2009) found that oxidative stress markers in liver did not differ between torpid and aroused arctic ground squirrels, and that oxidative stress was not associated with torpor in several tissues (including liver). In heart tissue, ROS that accumulate during torpor are counteracted by antioxidants released during the subsequent arousal (Wei et al, 2018). Thus, previous work suggests that neither the liver nor heart experiences a significant, enduring ROS load that might shorten telomeres.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence that both BAT and SM release antioxidants during torpor in European ground squirrels (Spermophilus citellus; Vucetic et al, 2013), ROS production in BAT is higher than that in SM in mice (Mailloux et al, 2011) andrats (Schönfeld andWojtczak, 2012); we presume a similar, tissue-specific ROS pattern is present in hibernating mammals. Additionally, the liver does not experience ROS-mediated oxidative damage during hibernation (Orr et al, 2009;Brown et al, 2012) and ROS production in the heart during late torpor is counteracted by antioxidants in the subsequent arousal episode (Wei et al, 2018). To test whether RTL shortened throughout hibernation, we sampled juvenile females at the middle (early January) and end (mid-March) of their hibernation season.…”
Section: Introductionmentioning
confidence: 99%
“…All animals were anaesthetized with 50 mg kg -1 sodium pentobarbital between 08:00 and 11:00 on the last day of the experimental period [19,30]. After the rapid removal of cardiac muscle, portions of the ventricles were immediately cut off and fixed in glutaraldehyde.…”
Section: Sample Preparationmentioning
confidence: 99%